The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1108/ijsi-12-2023-0139
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pre-existing cracks and concrete cover on service life of reinforced concrete and mechanical behaviour of corroded rebars

Kuleni Fekadu Yadeta,
Sudath C. Siriwardane,
Tesfaye Alemu Mohammed
et al.

Abstract: PurposeIncorporating pre-existing crack in service life prediction of reinforced concrete structures subjected to corrosion is crucial for accurate assessment, realistic modelling and effective decision-making in terms of maintenance and repair strategies.Design/methodology/approachAn accelerated corrosion test was conducted by using impressed current method on cylindrical specimens with varying cover thickness and crack width. Mechanical properties of the specimens were evaluated by tensile tests.FindingsThe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…According to the author, the study contributes methodological innovation by refining stress-strain models specifically for partially confined concrete, addressing the limitations of existing models, where the combination of experimental and simulated assessments using DIC and FEM technologies provides robust empirical evidence, advancing the understanding and optimization of FRP-concrete structure performance. Yadeta et al (2024) suggested a simple mathematical model for evaluation of the equivalent chloride ion diffusion coefficient considering crack width, average crack spacing and crack extending lengths for cracked reinforced concrete structures, which is used to incorporate existing crack in service life prediction models. In this research work, the authors conclude that the pre-cracked samples exhibited shorter concrete cover cracking times, particularly with wider cracks when compared to the uncracked samples, as well as the loadbearing capacity of the reinforcement bars decreased owing to the pre-cracks, causing structural deflection and a shortened yield plateau.…”
Section: Second Issuementioning
confidence: 99%
See 1 more Smart Citation
“…According to the author, the study contributes methodological innovation by refining stress-strain models specifically for partially confined concrete, addressing the limitations of existing models, where the combination of experimental and simulated assessments using DIC and FEM technologies provides robust empirical evidence, advancing the understanding and optimization of FRP-concrete structure performance. Yadeta et al (2024) suggested a simple mathematical model for evaluation of the equivalent chloride ion diffusion coefficient considering crack width, average crack spacing and crack extending lengths for cracked reinforced concrete structures, which is used to incorporate existing crack in service life prediction models. In this research work, the authors conclude that the pre-cracked samples exhibited shorter concrete cover cracking times, particularly with wider cracks when compared to the uncracked samples, as well as the loadbearing capacity of the reinforcement bars decreased owing to the pre-cracks, causing structural deflection and a shortened yield plateau.…”
Section: Second Issuementioning
confidence: 99%
“…Yadeta et al . (2024) suggested a simple mathematical model for evaluation of the equivalent chloride ion diffusion coefficient considering crack width, average crack spacing and crack extending lengths for cracked reinforced concrete structures, which is used to incorporate existing crack in service life prediction models.…”
Section: Second Issuementioning
confidence: 99%